Social media use and the challenges of information dissemination during emergencies: experience of library and information scientists on covid-19 in Nigeria (2020)
Corona virus is a form of respiratory ailment that ravaged human health and social interaction. Since its emergence and subsequent spread to various countries of the world, various governments, organisations, agencies and individuals have been making frantic efforts to curtail the disease using different media. Prominent among the media being used is social media. However, the preliminary investigation of the researchers indicated that the social media are being wrongly used to disseminate information on the emergence, causes, prevention and curtailment of the disease particularly in a developing country like Nigeria. The need to address these challenges and to drum home the contribution of Library and Information Scientists necessitated this study. Self-structured questionnaire administered at various online fora (NLA, NALISE and individuals) was the instrument used for the collection of data among the library and information scientists (librarians and library and information science educators). Total enumeration technique was employed to cover all the 201 respondents that participated in the survey monkey conducted. The study found that varying social media were being used to disseminate information about COVID-19. It was reported that library and information scientists are playing active role in enlighten masses on the danger of COVID-19, and has established an enduring relationship with the National Centre for Disease Control (NCDC) on the importance of library use as change agents. The need for Library and Information Scientists to sustain the use of social media while rendering information services especially in the time of pandemic such as COVID-19 was recommended.